Zinc agronomic biofortification of staple crops may be a cost-effective strategy to alleviate zinc deficiency in Ethiopia - Abdu, Abdu Oumer; De Groote, Hugo; Joy, Edward J. M.; Kumssa, Diriba B.; Broadley, Martin R.; Gashu, Dawd (Frontiers in Nutrition, 2022)
Background: Inadequate dietary zinc (Zn) supplies and Zn deficiency (ZnD) are prevalent in Ethiopia, where cereals are major dietary sources, yet low in bioavailable Zn. Zinc agronomic biofortification (ZAB) of staple crops through application of Zn fertilizers may contribute to alleviating ZnD. However, large-scale promotion and adoption of ZAB requires evidence of the feasibility and public health benefits. This paper aimed to quantify the potential cost-effectiveness of ZAB of staple crops for alleviating ZnD in Ethiopia. Methods: Current burden of ZnD among children in Ethiopia was quantified using a disability-adjusted life years (DALYs) framework. Evidence on baseline dietary Zn intake, cereal consumption, and fertilizer response ratio was compiled from existing literature and secondary data sources. Reduction in the burden of ZnD attributable to ZAB of three staple cereals (maize, teff, and wheat) via granular and foliar Zn fertilizer applications was calculated under optimistic and pessimistic scenarios. The associated costs for fertilizer, labor, and equipment were estimated in proportion to the cropping area and compared against DALYs saved and the national Gross Domestic Product capita-1. Results: An estimated 0.55 million DALYs are lost annually due to ZnD, mainly due to ZnD-related mortality (91%). The ZAB of staple cereals via granular Zn fertilizer could reduce the burden of ZnD by 29% and 38% under pessimistic and optimistic scenarios, respectively; the respective values for ZAB via foliar application were 32% and 40%. The ZAB of staple cereals via granular fertilizer costs US $502 and US $505 to avert each DALY lost under optimistic and pessimistic scenarios respectively; the respective values for ZAB via foliar application were US $226 and US$ 496. Foliar Zn application in combination with existing pesticide use could reduce costs to US $260–353 for each DALY saved. Overall, ZAB of teff and wheat were found to be more cost-effective in addressing ZnD compared to maize, which is less responsive to Zn fertilizer. Conclusions: ZAB of staple crops via granular or foliar applications could be a cost-effective strategy to address ZnD, which can be integrated with the existing fertilizer scheme and pesticide use to minimize the associated costs.